Clinicopathological Correlates of Lewy Body Disease: Fundamental Issues - Tae-Beom Ahn (Journal of Movement Disorders, 2010)
Lewy body pathology (LBP) is the pathological hallmark of Lewy body diseases, such as Parkinson’s disease and Lewy body dementia. Recent studies have shed new light on the role of LBP, the interactions of LBP with concomitant pathologies, and the propagation of LBP from the olfactory bulb and enteric nervous system to the central nervous system. The intrinsic difficulty with identifying clinicopathological correlates could be overcome by improving our understanding of the pathological evolution of LBP.